The Impact of the Turkish Presidential System on the Turkish Lira - Mahmut Zeki Akarsu (Journal of Banking and Financial Economics)
The political system always has a significant impact on economic indicators. Currency exchange is one of the indicators, which is influenced directly or indirectly by political developments. Investors and economic agents make investment decisions by not only economic outcomes but also political developments. Turkey is one of the countries, which can be an example of a domestic currency losing value significantly due to undemocratic political actions since the 2017 referendum. Therefore, in this study, the impact of the new presidential system on the Turkish Lira is investigated using the Bayesian structural time-series model in R software. According to the literature search, this study is the first article that analyzes how much the Turkish Lira decoupled negatively from peers and how badly the Turkish presidential system harms the Turkish Lira. According to the result, the undemocratic and unorthodox economic and political implementations cause the Turkish Lira to have dropped sharply and have decoupled negatively from other currencies significantly.